(untitled) (Central Asian Journal of Medical Sciences, 2021)
Objective: We aimed to assess the relationship between white blood cell count, pediatric appendicitis score and the measurement of the outer diameter of the appendix. Methods: The study was performed on 480 children admitted for suspected acute appendicitis and underwent an appendectomy at the National Center for Maternal and Child Health, Ulaanbaatar, Mongolia, between May 2019 and December 2019. Clinical diagnosis was performed using the pediatric appendicitis score based on the pre-operative blood test results, including white blood cell count, neutrophil count, lymphocytes count, and neutrophil-lymphocyte ratio. The diameter of the appendix was determined by ultrasound. Results: 516 pediatric patients (≤ 18 years old) were suspected of having acute appendicitis and subsequently underwent surgery. The pediatric appendicitis score and neutrophil-lymphocyte ratio were moderately correlated (r = 0.494), but the neutrophil-lymphocyte ratio and outer diameter of the appendix were poorly correlated (r = 0.169). In patients with an appendix outer diameter of ≤ 6 mm, 44% were inflamed, and 56% were not. Conclusions: Ultrasonic measurement of the outer diameter of the appendix had a 79.8% accuracy. This diagnostic accuracy can be enhanced with the combined usage of the pediatric appendicitis score and the neutrophil-lymphocyte ratio.